Nafkah Isteri dan Anak Pasca Perceraian Menurut Ulama, Kompilasi Hukum Islam dan Prakteknya di Pengadilan Agama - Zaini, Z (-, 2024)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family or household, or often referred to as Sakinah, mawaddah warahmah. However, sometimes marriages fail and break up in the middle of the road. As a result, the wife and children often bear risks, such as living costs (subsistence), education costs, housing and so on. This article aims to find out the income for wives and children after divorce according to scholars, Compilation of Islamic Law and Post-divorce in the Religious Courts. The methods used are normative and empirical research, meaning looking at the normative legal side and also practice in the field. It is the husband's obligation to provide support for his wife during the iddah period, wages for looking after their children, and support for the children themselves until they reach adulthood so that the children are independent. And in practice, the Religious Court will grant requests for maintenance for wives and children after divorce, if submitted when filing a court lawsuit, although sometimes the amount is different from that proposed in the lawsuit.